THE IMPLEMENTATION OF PICTURE SERIES TO IMPROVE STUDENTS SPEAKING ABILITY AT THE SECOND GRADE OF SMP MUHAMMADIYAH 3 JETIS PONOROGO IN ACADEMIK YEAR 2016/2017 - Sri Wahyuni; Niken Reti Indriastuti; Dyah Atiek Mustikawati (EDUPEDIA, 2018)
This study was  porpused to know how picture series method can improve students’ speaking skill ability at the second grade of SMP Muhammadiyah 3 Jetis Ponorogo in academic year 2016/2017. This study used classroom action research and implemented picture series as the media in teaching speaking. This technique applied to the students in second grade of SMP Muhammadiyah 3 Jetis Ponorogo in acedemic year 2016/2017 that consist of 18 students. This research conducted on February  22nd  2017- June  15th  2017. The steps of the strategy began from the students observed some pictures that showed by the teacher, devided the class into groups, then, each groups got picture to describe, the last the students presented the picture orally one by one. After the researcher conducted the research, the result of the test showed that the mean of students’ score  in the first cycle was 64.88 and the mean of students score in test II was 78. The result of questionnaire of the first cycle was 85% and the second cycle was 87%. Furthermore, the result of observation checklist in second cycle was 85%  showed that the students active in speaking activity in classroom. The data that was obtained in each cycle explained that the students’ score in  speaking were increase. Finally, The researcher gives sugestion to the teacher that picture series considered as interesting media, so it can as an alternative media to teach speaking skill and the researcher hopes this research result can use as the  refference for the next researcher.